How does a Social and Behavioral Change Communication Intervention Predict Menstrual Health and Hygiene Management: A Cross-Sectional Study - Astha Ramaiya; Alka Malhotra; Carmen Cronin; Sarah Stevens; Kelli Kostizak; Animesh Sharma; Shailesh Nagar; Suruchi Sood (BMC, 2019)
Abstract Background Interventions in India to improve menstrual health and hygiene management (MHHM) have been implemented at the national, state, district and school level. However, evaluations of these interventions have been scarce. The objective of the study was to determine if a social and behavioral change communication (SBCC) intervention (GARIMA) had a relationship with knowledge, attitudes, interpersonal communication, restrictions and MHHM using a comparison group post-test only design among 2206 adolescent girls. Methods Intervention villages and adolescent girls were selected through stratified random sampling based on where GARIMA was implemented. Villages and adolescent girls in comparison villages were matched socio-demographically to intervention villages and adolescent girls. Multi-level logistic regressions assessed the relationship between the encoded exposure, mediators and MHHM. Results The results showed that the encoded exposure predicted all behaviors corresponding to MHHM. Additionally, adolescent girls in the high encoded exposure group had significantly higher knowledge about puberty and reproductive parts (AOR: 2.03 (95% CI: 1.31 - 3.15)), positive attitudes towards gender (AOR: 1.48 (95% CI: 1.02 - 2.16)) and higher levels of some discussion and dialogue (AOR: 1.41 (95% CI: 1.04 - 1.92)). Conclusions Future programs should use SBCC to improve MHHM behavior but involve families, peers and community members to a greater extent in order to improve attitudes towards menstruation, attitudes towards restrictions, attitudes towards absorbent use and reduce restrictions within the community.